2003
DOI: 10.1007/s00220-003-0793-9
|View full text |Cite
|
Sign up to set email alerts
|

New Solutions of Einstein Equations in Spherical Symmetry: The Cosmic Censor to the Court

Abstract: A new class of solutions of the Einstein field equations in spherical symmetry is found. The new solutions are mathematically described as the metrics admitting separation of variables in area-radius coordinates. Physically, they describe the gravitational collapse of a class of anisotropic elastic materials. Standard requirements of physical acceptability are satisfied, in particular, existence of an equation of state in closed form, weak energy condition, and existence of a regular Cauchy surface at which th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 18 publications
2
75
0
Order By: Relevance
“…Nevertheless, the CCC remains unproved and there exists no mathematically precise and definite statement for the CCC which one could try to prove (see e.g. [1][2][3][4][5][6] for some recent reviews, and references therein).…”
mentioning
confidence: 99%
“…Nevertheless, the CCC remains unproved and there exists no mathematically precise and definite statement for the CCC which one could try to prove (see e.g. [1][2][3][4][5][6] for some recent reviews, and references therein).…”
mentioning
confidence: 99%
“…Subsequently, the area-radius framework has been successfully applied to models of gravitational collapse and cosmic censorship (see e.g. [13,18,30]). …”
Section: Reduction Of the Field Equations Tomentioning
confidence: 99%
“…[16,18,20,21]). Besides the details of the physics of the collapse of such systems, the general pattern arising from all such examples is that existence of naked singularities persists in presence of stresses: actually, we have recently shown that the mechanism responsible for the formation or whatsoever of a naked singularity is the same in all such cases [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…scalar fields [15][16][17][18], perfect fluids [19][20][21][22][23][24], imperfect fluids [25][26][27][28] and null strange quark fluids [29,30]. The analysis has also been taken to wider gravitational settings, such as f (R) theories [31], Lovelock gravity [32] (see also [33][34][35][36][37][38] for some recent reviews) and hypothesized quantum gravity theories . This is an interesting line of research because, the possible discovery of naked singularities may provide us with an opportunity to extract information from physics beyond trans-Planckian regimes [69]; see e.g.…”
Section: Introductionmentioning
confidence: 99%